Chemsex: Emerging Threats Facing the MSM Experience - A Cross-Sectional Study - Ly, Anh Huy; Huynh, Minh Truc; Dap, Thanh Giang; Dinh, Cong Thuc; Luu, Bao Chau Huynh; Bui, Phuong Oanh Ngoc; Le, Quang Thu; Khuu, Van Nghia; Nguyen, Tan Dat; Nguyen, Tuyen Thi Hong (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The trend of male homosexuality is progressively rising. The preference for chemsex (use of recreational drugs during sexual encounters) is also becoming more prevalent among the men who have sex with men (MSM), which increases sexual excitement during intercourse. This, in turn, heightens the risk of transmission of sexually transmitted diseases, including HIV/AIDS. Objective. To assess the prevalence of chemsex in same-sex relationships and related behaviors among MSM. Subjects and methods. A cross-sectional study was conducted on 227 MSM in the community of Can Tho city, Vietnam, from March to October 2023. Results. 42.3% of MSM engage in chemsex. The most commonly used substance in chemsex is popper (94.8%). Six factors are associated with chemsex: (a) MSM working in office jobs (OR = 2.1, 95% CI 1.1 - 4.3, p = 0.030); (b) Having more than 5 sexual partners (OR = 7.2, 95% CI 2.6 - 20.1, p < 0.0001); (c) Engaging in sex work or exchanged sex for money (OR = 5.0, 95% CI 1.3 - 18.6, p = 0.017); (d) Participating in group sex (OR = 5.2, 95% CI 2.4 - 11.4, p < 0.0001); (e) Never using condoms during sex (OR = 1.5, 95% CI 1.2 - 2.0, p = 0.003); and (f) Using recreational drugs (OR = 1.9, 95% CI 1.1 - 3.5, p = 0.024). Factors influencing chemsex behavior include easy access to stimulants, lack of understanding about the harms of chemsex, trust in sexual partners, desire to enhance sexual pleasure, and pain reduction during intercourse. Conclusion. Chemsex among the MSM group is on the rise, and this likely leads to increased rates of HIV and STI transmission, as well as long-term health consequences. Healthcare workers and the community need to reduce stigma, discrimination, and narrow-minded attitudes towards individuals who use substances during sexual activity, as these barriers can prevent them from seeking harm reduction information and professional assistance for the issues they face